Supply Chain Management and Logistics in Latin America : A Multi-Country Perspective. - Yoshizaki, Hugo Tsugunobu Yoshida; Velázquez Martínez, Josué C.; Mejia-Argueta, Christopher (Bingley : Emerald Publishing Limited, 2018)
Latin America is a fast-growing market, but its poor infrastructure, explosive urbanization, expensive and inefficient logistics, and multiple social problems continue to pose major problems to logistics professionals and academics. Here leading scholars across Brazil, Colombia, Cuba, Ecuador, Peru, Panama, and the USA address these issues.
Chapter 9 The São Paulo Off-Hour Delivery Pilot: Impacts for City Logistics -- Introduction and Context -- Literature Review -- Case Description -- Results -- Noise -- Safety -- Traffic and Truck Speeds -- Costs and Productivity -- Concluding Remarks -- References -- Chapter 10 Solutions for Enhanced Commercial Logistics in Cities - A Case Study of Two Different Zones in Quito - Ecuador -- Introduction -- Description of Historic Center and La Mariscal in Quito - Ecuador -- Application of Urban Logistics -- Experimental Test Rig, Measurement Techniques, Methodologies -- Data Collection and Preparation -- Data Extrapolation -- Stores and Streets Weights -- Optimization Model -- Simulation Model -- Mathematical Modeling -- Formula 1: Sample Size -- Formula 2: Analytical Hierarchy Process -- Formula 3 Optimization Model -- Results and Discussion -- Data Collection and Preparation Results -- Optimization Model Results -- Simulation Model Results -- Discussion and Conclusion -- References -- Chapter 11 Financial Risk Measurement in a Model of Supply of Raw Materials -- Introduction -- Methodology -- Results and Discussion -- Conclusion -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Business logistics-Latin America-Congresses.; Electronic books